"The suits care about us": employee perceptions of workplace chaplains. Issue 5 (20th October 2018) - Miller, David W.; Ngunjiri, Faith Wambura; Lorusso, James D.
ABSTRACT: Workplace chaplaincy is an intriguing phenomenon, wherein organizations hire clergy persons to serve the social, spiritual, and psychological needs of their employees. The authors interviewed 56 employees in nine organizations to explore employee perceptions and experiences with chaplaincy. The results indicate that employees perceive chaplaincy as a demonstration of management's care and concern for then as whole persons by having chaplains meet their work and nonwork needs. Employees report that workplace chaplains care for them in five ways: attending to their work-related issues; addressing their practical and social needs; meeting their psychotherapeutic needs; facilitating urgent care as first responders in a crisis; and providing religious or pastoral services. The study suggests that employees' experience of such care from chaplains can be interpreted as perceived organizational support, which enhances their sense of well-being and their organizational commitment. The article concludes with recommendations for future research.